Women's pictures feminism and cinema - Kuhn, Annette (London Boston Routledge & Kegan Paul, 1982)
In this exploration of the relationship betwen feminism and cinema, the author discusses the issues, explains the analytical terms and examines the alternatives for feminist film analysis and film making. The films used as points of discussion are drawn from both mainstream and alternative cinema.
Includes index.
Includes bibliographical references and index.
CMC-2885 donated by Prof. Ellen J. Paglinauan.
Keywords: Feminism and motion pictures; Women in motion pictures